Modifications in pedaling kinematics, saddle pressures and comfort in elite cyclists after alterations in saddle height during ventilatory thresholds - Encarnación-Martínez, A.; Sendra-Pérez, C.; Mateo-March, M.; Pérez-Soriano, P. (Journal of Sports Sciences, 2025)
Clear evidence is lacking in cycling biomechanics research regarding the effects of pedaling at various saddle heights (SH) and intensities, hindering full comprehension of bicycle geometry configurations and their impacts on performance and potential injuries. The aim of the study was to evaluate the effect of changes in SH (freely chosen, +2%, and -2%) at two intensities (First (VT1) and second (VT2) ventilatory threshold) on the pressures exerted on the saddle, the lower-limb kinematics, and perceived comfort. Twenty-four elite cyclists pedaled for 6 min on an ergometer at each of the saddle heights and intensities. The results of the kinematics showed differences (p < 0.05) as a function of the SH in all the variables analyzed. The results of the saddle pressures showed an interaction between SH and saddle zones (p < 0.01) depending on intensity (p = 0.002). There were higher levels of overall perceived comfort in freely chosen SH. In conclusion, higher SH (+2%) produced greater pressures on the saddle, greater extension in the lower extremities, and less comfort for the cyclist. Regarding intensities, VT2 reduces the pressures exerted on the saddle, leading to increased ankle dorsiflexion and decreased hip flexion-extension which negatively impacts cyclist comfort when not pedaling at freely chosen SH.